What is editorialization? - Vitali Rosati, Marcello (Sens public)

(untitled) (Département des littératures de langue française, 2016)
This paper is the result of eight years of work on the concept of editorialization that was done in the context of the international seminar “Écritures numériques et éditorialisation”, which I have been co-organizing with Nicolas Sauret since 2008. I propose a definition of editorialization as the set of dynamics that produce and structure digital space. These dynamics can be understood as the interactions of individual and collective actions within a particular digital environment. Starting from this definition I try to describe how authority works in digital space.